Heat transfer analysis of underground Maju Cable Tunnel / Lim Shin Fong - Lim, Shin Fong (2018)
This study emphasized on utilizing numerical method to determine the best ventilation method and best air flow rate for Underground Maju Cable Tunnel ventilation system. The purpose of this mechanical ventilation system is to remove the heat produce by the high tension cables in this unmanned cable tunnel and same time maintain the cable tunnel internal temperature below 40° to ensure a steady state operation condition. In this 163m long, 3m width and 2.4m height rectangular cable tunnel, there are 4 circuits of XLPE 132KV 3x1C 1000mm2 (copper conductor) mounted in this cable tunnel and each circuit were installed in trefoil configuration. By analytical calculation, the surface temperature of the XLPE cable is approximately 56.25°C. However, surface temperature of 60°C to be applied in the simulations in order to simulate the worst case scenario. CFD software - ANSIS fluent was used for simulations and it was preset to simulate in Steady State Condition. Simulations were conducted in two types of conventional ventilation method which are Longitudinal Ventilation and Semi Transverse Ventilation. Two different air change rate, 10 Air change per hour (ACH) and 20 ACH have been applied to simulate with two different ambient temperature, 33.63°C (which is average ambient temperature in Klang Valley) and 37.00°C (10% above average ambient temperature). The purpose of simulating in a 10% above average ambient temperature is to ensure the design air flow rate could maintain the tunnel internal temperature even if global temperature rise in future. In total, 8 scenarios have been simulated. From the analysis results, it can be conclude that the most suitable ventilation method is Longitudinal Ventilation for such length cable tunnel. The most suggested inlet air velocity is 0.9055m/s (20ACH) with the air flow of 23470.56 CMH. With this setup, the internal ambient air temperature below 40°C can be achieved. At this temperature, the heat generated by high voltage cables can be dissipated efficiently and maintain in a high performance current carrying capacity.